Role Playing Method To Improve English Speaking Four Grade Students In MIM Sajen Tahun 2021/2022 - Suryanti, Erna (Universitas Sebelas Maret, 2022)
This research aims to improve the mastery of English Speaking in grade 4 students at MIM SAJEN in 2021/2022. The mastery referred to in this research is improving mastery of English using Role Playing to make it easier for students to learn Speaking.The subjects in this research were 21 class IV students at MIM SAJEN. The method used was the Classroom Action Research method with a research design according to Kemmis and Taggart. The data collection method used is using student activity observation sheets and test questions for speaking performance. The data analysis technique used in this research is quantitative and qualitative descriptive analysis. The results of the research show that using ROLE PLAYING can improve the mastery of English speaking in class IV MIM SAJEN students. The increase in speaking mastery is proven by the average pre-test score of 15.7 (poor category), cycle 1 of 53.1 (sufficient category). ), cycle II was 68.8 (good category). Apart from these results, students also became more fluent in speaking using English vocabulary in front of other students.